The Oyambre coastal terrace: a detailed sedimentary record of the Last Interglacial Stage in northern Iberia (Cantabrian coast, Spain). (14th May 2021) - Sainz de Murieta, Elisa; Cunha, Pedro P.; Cearreta, Alejandro; Murray, Andrew S.; Buylaert, Jan‐Pieter
ABSTRACT: A detailed study is presented of a 15.3‐m‐thick Pleistocene coastal terrace located on the Cantabrian coast (northern Spain). Stratigraphic, sedimentological, topographic and micropalaeontological information is combined with a chronology based on luminescence dating to characterize the deposits. The sedimentary succession records: (i) a basal transgressive system, consisting of a wave‐cut surface covered by a lower layer of beach gravels and upper beach pebbly sands; and (ii) a thicker upper highstand system (aggrading), comprising medium to very fine aeolian sands interbedded with thin palustrine muds. Luminescence dating involved a detailed sampling strategy (36 samples and two modern analogues) and the use of both quartz optically stimulated luminescence (OSL) and feldspar post‐infrared infrared stimulated luminescence single aliquot regeneration protocols; feldspar results were used to confirm the completeness of bleaching of the quartz OSL signal. The quartz OSL luminescence age–depth relationship shows significant dispersion, but nevertheless two rapid phases of deposition can be clearly identified: one at 130 ka [Marine Oxygen Isotope Stage (MIS) 5] and one at 100 ka (MIS 5c). The top of the succession is dated to 70 ka. The MIS 5e marine maximum flooding surface is identified at an elevation of 6.85 m above mean seal level. This elevation provides evidence of a regional sea‐level highstand for this sector of the Cantabrian coast.